Youth, political violence and ZANU-PF politics in Zimbabwe, c.1950-2018 - Munyarari, Tinashe (Rhodes University, Faculty of Humanities, Department of History)
This study is a socio-political aspect of Zimbabwean history. It examines the development of youth political violence starting from the late 1950s when violent forms of African political mobilisation emerged to 2018 when the first election without Robert Mugabe was held. It explores how early nationalist parties such as the Salisbury City Youth League (SCYL), Southern Rhodesia African National Congress (SRANC), National Democratic Party (NDP), Zimbabwe African People's Union (ZAPU) and later the Zimbabwe African National Union (ZANU) mobilised and socialised youths into political violence to understand the roots of the violent political culture in Zimbabwe. This study shows that youths were an important part of the strategies of these political parties in countering the violence of the colonial state as well as mobilising mass support for the movements during the liberation struggle. It reveals that war collaborators (mujibhas and chimbwidos) were central role players in instigating political violence against innocent and defenceless people during the war. In the 1980s and 1990s, the Youth brigades and the ZANU-PF Youth League became a key constituent for state-socialist developmental goals but they were at times manipulated as a resource for political violence when Mugabe's power was challenged. The study shows that more grotesque violence occurred in the 2000s era when the National Youth Service (NYS) was introduced and state-sanctioned vigilante groups like Chipangano in Mbare emerged in response to the rise of the Movement for Democratic Change (MDC) and diminishing of consensual power. This study argues that youth were not mere victims and perpetrators of political violence, but they were a collection of various interest sub-groups with diverse agendas and a sense of agency. Some joined violent groups for their social mobility, power, impunity and economic opportunities availed to the group members. Data for this study was drawn from Mbare and Highfields (in Harare Province) and Uzumba-Maramba-Pfungwe (in Mashonaland East Province).
Keywords: Youth protest movements Zimbabwe; Political violence Zimbabwe; ZANU-PF (Organization : Zimbabwe); Agent (Philosophy); Zimbabwe Politics and government; Zimbabwe History